8. ASSOCIATED RISK FACTORS AT THE SURGICAL SITE INFECTIONS POSTCESAREAN SECTION AT THAI NGUYÊN GENERAL HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: Identify some factors related to the results of using antibiotics to prevent surgical site infections in pregnant women post-cesarean section at Thai Nguyen General Hospital in 2022. Subject and method: A cross-sectional descriptive study on pregnant women who were indicated for cesarean section with prophylactic antibiotic Cefoxitin 1g slow intravenous injection at the Obstetrics Department, Thai Nguyen General Hospital. Result: There were 184 pregnant women were indicated for cesarean section, with an average age of 28.36±5.0. The success rate after surgery was 98.4% (181/184) with 1.6% of cases with NKVM having to change the regimen (3/184), of which all three cases of NKVM were superficial infections. Factors related to surgical site infection (p < 0.05) included: Age (> 35 years old), number of births (≥2 time), and length of hospital stay (≥7 days). Conclusions: The success rate after MLT in pregnant women using KSDP at Thai Nguyen Central Hospital was relatively good at 98.4%, however, attention should be paid to the risk factors for surgical site infection after surgery such as age groups, number of births, length of hospital stay.
Keywords: Surgical site infection, caesarean section, risk factor associated post-cesarean section.